2007 ASME boiler & pressure vessel code : an international code. Section II, (American Society of Mechanical Engineers, 2008)
The international boiler and pressure vessel code establishes rules of safety governing the design, fabrication, and inspection of boilers and pressure vessels, the content is full-text searchable.
"July 1, 2008."
Includes addenda for 2008.
Keywords: Steam-boilers -- United States -- Design and construction.; Steam-boilers -- Standards -- United States.; Pressure vessels -- Design and construction.; Pressure vessels -- Standards -- United States.; Nuclear power plants -- United States -- Design and construction.; Nuclear power plants -- Standards -- United States.; elektronické knihy; electronic books